Truth and Responsibility: A Personalist Reading of Newman - Kłos, Jan (Brill, 2024)
This book goes beyond a simple study of Newman’s thought and work and seeks to apply his deductions to modern value conflicts. Although it will be of particular relevance to academic readers with some prior knowledge of Newman’s works, it may also be of wider interest to students of history, philosophy, theology and spirituality. More generally, its unusual focus on Newman’s epistemology and philosophical deductions, and how these relate to present-day dilemmas, should also attract interest from his many non-academic followers and devotees.